Biomechanical Evaluation of Pediatric Anterior Cruciate Ligament Reconstruction Techniques with and without the Anterolateral Ligament. Issue 7 (21st July 2017) - Pace, James Lee; Trentacosta, Natasha E.; Metzger, Melodie; nelson, trevor; Michalski, Max; Polakof, Landon S.; Mandelbaum, Bert R.
Objectives: Management of anterior cruciate ligament (ACL) injuries in skeletally immature patients is controversial and several surgical procedures have been developed. The two most popular physeal sparing procedures are the iliotibial band (ITB) ACL reconstruction (ACLR) and the all-epiphyseal (AE) ACLR. There has been some concern for over-constraint of the knee with the ITB ACLR while the AE ACLR is technically challenging and can still risk growth disturbance. There has been interest recently into the anterolateral ligament (ALL) and its role in rotational stability, but it has not been assessed in the setting of pediatric ACLR techniques. The ITB ACLR includes a lateral tenodesis of the IT band to the femur that closely approximates the ALL. Our hypothesis is that the ITB ACLR and AE ACLR with ALL reconstruction (ALLR) will best replicate the biomechanics profile of the intact ACL. Methods: Eight cadaveric legs were statically loaded with an anterior drawer force and varus, valgus, internal and external rotational moments at 0°, 30°, 60°, and 90° of flexion. Displacement and rotation was recorded in the following conditions: intact ACL/intact ALL, ACL deficient/intact ALL, ITB ACLR/intact ALL, ITB ACLR/ALL deficient, ACL deficient/ALL deficient, AE ACLR/ALL deficient, AE ACLR/ALLR. Results: Both ACLR techniques reduced anterior translation from the ACL deficient state but neither restored translation to the intact state (p<0.05) except in full extension. ALL deficiency increased anterior translation in the ACL deficient state (p<0.05). In rotational testing, only the ACL deficient/ALL deficient state had a significant increase in internal rotation (p<0.05). This was significantly restored at all flexion angles with the ITB ACLR. There was no rotational over-constraint in any flexion angle with the ITB ACLR. The AE ACLR/ALL deficient state and AE ACLR/ALLR improved rotational stability at lower flexion angles, but not at 60° and 90°. There were no significant changes in varus/valgus moments. Conclusion: In this model, the ITB ACLR best corrected both parameters at all angles without over-constraining the knee and without the need for an ALLR. The AE ACLR and AE ACLR/ALLR improved both parameters but not at all flexion angles. The ITB ACLR appears to be the simpler pediatric ACLR technique to regain translational and rotational stability. ALL deficiency in the knee increased anterior displacement and rotational moments in the ACL deficient state.